A phase II clinical evaluation of radiofrequency ablation (RFA) combined with regorafenib and toripalimab in patients with colorectal cancer with liver metastases - Ouyang, Hui; Luo, Huiyan; Gao, Fei; Mie, Man; Ren, Chao; Li, Ji-Bin; Fu, Haiyan; Huang, Jin Shan (Journal of clinical oncology, 2024)
3566Background: In several clinical studies, the combination of anti-programmed cell death protein 1 (anti-PD-1) antibodies with targeted antiangiogenic agents has demonstrated clinical benefits for patients with metastatic colorectal cancer (mCRC). However, individuals with liver metastases have shown suboptimal responses. Prior preclinical study indicates a synergistic efficacy of radiofrequency ablation (RFA) when employed in conjunction with immunotherapy. The study aimed to explore whether RFA combined with regorafenib and toripalimab (an anti-PD-1 antibody) could provide better outcomes in patients with colorectal cancer liver metastases. Methods: Using Simon's two-stage design, a total of 32 subjects were required for enrollment, with10 subjects included in stage 1. If there were no or less patients having response, the study would be terminated; otherwise, it would proceed to stage 2, enrolling an additional 22 subjects. The cohort consisted of 10 microsatellite stable (MSS) mCRC patients with multiple liver metastases who had previously failed fluorouracil, oxaliplatin, irinotecan, with or without targeted therapy. RFA was performed on a single hepatic lesion, with others designated as target lesions. Treatment with regorafenib and toripalimab commenced one week post-RFA, following a 4-week cycle. Toripalimab was administered intravenously biweekly, and regorafenib was given orally at daily dose of 80 mg (three weeks on, one week off, in a 4-week period). The primary endpoint was response rate. Results: Ten patients (3 women) were enrolled in this study, with ages ranging from 26 to 76 years (median: 52 years), and 60% being 52 years or older.Seventy percent had ECOG performance status (PS) of 0; 60% had primary colon tumors; 90% presented with synchronous liver metastases, and 80% had both intrahepatic and extrahepatic metastases. Half of the participants achieved stable disease; however, none exhibited confirmed partial or complete responses. The median progression-free survival was 3.3 months, and the median overall survival reached 11.3 months. The median number of cycles was two (range: 0.5 to 3), with 60% undergoing at least two cycles. Adverse events (AEs) included hand-foot syndrome, liver dysfunction, fatigue, abdominal distension, and thrombocytopenia. The most frequently reported AE was hand-foot syndrome, occurring in 50% of patients. Serious AEs (grade≥3) potentially related to treatment included hand-foot syndrome and hyperbilirubinemia, each with an incidence of 10%. Notably, one patient experienced hyperprogression during immunotherapy. Conclusions: The combination of RFA, regorafenib, and toripalimab has not shown encouraging efficacy in patients with CRC liver metastases. However, the observed safety profile is acceptable. Clinical trial information: NCT05485909.